KERAGAMAN DAN PENERIMAAN MAKANAN ANAK BERPENGARUH PADA STUNTING DI DESA LOKUS STUNTING KABUPATEN ENREKANG : STUDI POTONG LINTANG - Sirajuddin; Agustian Ipa; Trina Astuti; Ulti Desmarnita (Media Gizi Pangan, 2023)
Dietary Diversity Score (DDS), Acceptance Diet (AD) and Minimum Meal Frequency (FFM) of children's are direct variables that affect nutritional status. The objectives of this study was to determine the effect of DDS, FFM and  AD on stunting in children aged 1-3 years. The Design is a cross-sectional study, conducted in Baraka District, Enrekang South Sulawesi Indonesia. Measurement of height using a microtoice (2-3) years and a length board (2 years) with an accuracy of 0.1 cm. Stunting was determined according to the 2006 WHO anthropometric median, <-2 SD HAZ. The child feeding instrument uses the WHO/Unicef ​​instrument, 2021. Bivariate analysis used Chi Square Test, multivariate analysis used Logistics Regression. The results of the study found that the gender and father education had an effect on stunting (p=0.000) and p=0.018, while the age group (p=0.946), mother's occupation (p=0.392), mother's education (p=0.190) had no effect to prevention of stunting. Child feeding consisting of FFM, DDS and AD partially affected stunting p<0.05. Logistic regression analysis revealed that stunting can be predicted by modeling by 73.5% used strong predictors of risk factor DDS, and  AD. Odds ratio 95% (CI) is 4.18 (1.69-10.33), p = 0.02 and 41.60(16.5-104.3) and protective by female Odds Ratio 95% CI= 0.30(0.12-0.71), p=0,007,  Meanwhile, FFM and father education cannot predict stunting p=0.062 and p=0,442 respectively. Conclusion: stunting in Baraka sub-district is influenced by DDS, AD and Sex. It is recommended to strengthen education on the DDS and AD children to prevent stunting in children aged 1-3 years